2017
DOI: 10.1152/ajpheart.00816.2016
|View full text |Cite
|
Sign up to set email alerts
|

The carotid baroreflex modifies the pressor threshold of the muscle metaboreflex in humans

Abstract: The purpose of the present study was to test our hypothesis that unloading the carotid baroreceptors alters the threshold and gain of the muscle metaboreflex in humans. Ten healthy subjects performed a static handgrip exercise at 50% of maximum voluntary contraction. Contraction was sustained for 15, 30, 45, and 60 s and was followed by 3 min of forearm circulatory arrest, during which forearm muscular pH is known to decrease linearly with increasing contraction time. The carotid baroreceptors were unloaded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Therefore, our findings of an attenuated pressor response to metaboreflex activation in the upright position support the concept that activation of the arterial baroreflex acts as a “brake” for the metaboreflex (as proposed by (Ichinose et al. ) and (Calbet et al. )).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, our findings of an attenuated pressor response to metaboreflex activation in the upright position support the concept that activation of the arterial baroreflex acts as a “brake” for the metaboreflex (as proposed by (Ichinose et al. ) and (Calbet et al. )).…”
Section: Discussionsupporting
confidence: 90%
“…Using either a neck pressure device (Ichinose et al. ) or the seated position (Teixeira et al. ) previous studies have suggested that unloading of baroreceptors should increase the function of the metaboreflex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations